Detection and genotyping of Leptospira spp. from the kidneys of a seemingly healthy pig slaughtered for human consumption - Ashutosh Verma; Esteban Soto; Oscar Illanes; Souvik Ghosh; Carmen Fuentealba (Journal of Infection in Developing Countries)
Introduction: Leptospirosis is a zoonotic disease caused by pathogenic Leptospira spp.  Leptospirosis is maintained in an environment due to chronic kidney infection of a wide variety of domestic, peridomestic and wild reservoir mammals. In this study the role of pigs in maintenance of leptospires on the Caribbean island of St. Kitts was investigated. Methodology: The condemned kidneys of 60 pigs slaughtered at a St. Kitts abattoir were screened by a quantitative-PCR for the presence of Leptospira spp. Positive samples were genotyped using a six-gene based multilocus sequence typing scheme. Results: Leptospiral DNA was detected in the kidneys of one of the 60 pigs. Multilocus sequence typing identified the infecting species to be L. interrogans. Conclusions: Detection of this zoonotic pathogen in the kidneys of a seemingly healthy pig raises concerns regarding the subclinical carriers of the disease among the island’s swine population.